اراضی بیت المال کی آبادکاری:تحقیقی مطالعہ: Bait-ul-Mall’s Land Cultivation A research based study - Hafiz Saif Ul Deen; Dr. Hafiz Taj Afsar (MEI, 2023)
Land has a key status among all economic recourses .The ownerless land is owned by the state, such type of land is called Bait-ul-Mall’s land. The central treasure of an Islamic state is called Bait- ul-Mall. Islam favors the cultivation of such land for economic wellbeing of public. It is important to make the state wealthy from agricultural production .It is therefore, necessary that the ownerless or uncultivated land should be cultivated, and no this connection? What should state do to cultivate such land? This article discusses different means to take steps for this purpose.